Development of Simulink Model to Investigate Control Structure, Safety, and Stability of a Water Brake System at Main Engine in House 5 Laboratory: Warnemünde - Axel Rafoth; Wolfgang Busse; Muhammad Tri Kurniawan (International Journal of Marine Engineering Innovation and Research, 2019)
A water brake loads the diesel engine will set desired work points and work curves. So that can find a safe point and control safety. After this, the essential system component will be created the model in block diagram and the block diagram will be simulated with Simulink. This requires a model of combustion machine and its control as well as break system and its control. The valve angle also affects the amount of flow or discharge of water which resides in the brake system. The amount of water flow in the brake system affects the amount of load that will be accepted by the main engine. The model is to be validated with measured data. To define load characteristics for a parallel operating visualization, these load characteristics are to be simulated. The results of the modeling were to know PI controller parameters to control the main engine. In the investigation, then simplify the process of modeling results are displayed in the form of a curve. Where in the curve we can see the performance of the engine and brake system so that the operation of the main engine will get maximum condition within safe limits.